EFFECTIVE LEADERSHIP IN SECONDARY SCHOOL EDUCATION MANAGEMENT: A TEACHER’S PERSPECTIVE IN GORONTALO - Yahya Yunus Anuli; Buhari; Baso Tola (Tadbir: Jurnal Manajemen Pendidikan Islam, 2023)
In the context of education in Gorontalo, there are still limitations in the implementation of effective leadership, especially in the design and implementation of learning in the field. This study aims to analyze the influence of leadership on changes in education management at the secondary school level. The approach used was quantitative, involving 562 secondary school teachers as randomly selected respondents. Data collection was carried out through instruments with an assessment scale of 1 to 5, and data analysis used SPSS-assisted descriptive statistics version 25.0 to calculate the average value and the relationship between variables. The results showed that all dimensions of leadership were in the high category, with an average score that described the level of confidence of teachers in the implementation of leadership that was classified as good. These findings confirm that the role of leaders contributes significantly to driving positive changes to education management in secondary schools. In conclusion, the application of leadership styles needs to be strengthened and maintained between old and new leaders so that the effectiveness of learning in junior high school can increase. The implications of this study highlight the importance of leadership training and development for teachers to improve the quality of management, planning, and implementation of learning in schools